Degradation studies on paraquat malathion using tio2/zno based photocatalyst - Ali, Rusmidah (2008)
Paraquat, a herbicide and malathion, an insecticide are pesticides that are always polluting our water system. Thus a lot of efforts has been conducted to treat the pollu ted water. The latest technology proposed is using photocatalyst. In this study, ZnO and TiO 2 were used as photocatalysts to degrade the pesticide in the presence of UV light ( λ =354 nm). The photodegradation rate was measured using UV-Visible spect rophotometer and TOC analyzer. Malathion showed the absorption peak at λ =210 nm while for paraquat at λ =258 nm. The best coupled photocatalyst for degrading malathion solution is ZnO/TiO 2 with % weight ratio 1:0.05 and the best coupled photocatalyst in degrading paraquat solution is TiO 2 /ZnO with % weight ratio 1: 0.03. The result shows that Fe 2+ ion present in the reaction mixture was better than Fe 3+ ion present as a dopant (which is added during the catalyst prep aration). The opt imum photocatalys t calcinations temperature for degrading paraquat and malathion were 550°C for TiO 2 and 500°C for ZnO. The physical prop erties of the best catalyst were characterized using SEM, XRD, UV-Vis-NIR spectrophotometer and elipsometer. By increasing the calcinations temperature up to 600°C, XRD data showed the transformation of TiO 2 anatase to rutile phase while for ZnO, the increment of the intensity of ZnO catalyst was observed, indicating that, the quali ty of ZnO wurtzite crystal wa s improved. The thicknesses for ZnO, ZnO/TiO 2 1:0.05 and ZnO/TiO 2 doping with Fe 3+ thin film were 130.57 nm, 150.68 nm and 153.84 nm respectively. The band gap energy values measured using UV-Vis NIR were in the range of 2.95 – 3.09 eV.